2010
DOI: 10.3926/jiem.2010.v3n1.p176-198
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability (HRV) biofeedback: A new training approach for operator’s performance enhancement

Abstract: The widespread implementation of advanced and complex systems requires predominantly operators' cognitive functions and less importance of human manual control. On the other hand, most operators perform their cognitive functions below their peak cognitive capacity level due to fatigue, stress, and boredom. Thus, there is a need to improve their cognitive functions during work. The goal of this paper is to present a psychophysiology training approach derived from cardiovascular response named heart rate variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 12 publications
0
41
2
2
Order By: Relevance
“…Most of the participant that had been undergone the training previously had been significantly resulted in a better HRV amplitude than before. Maximal performance control over the HRV can be obtained after series of approximately four sessions of training [12]. The students that have the good result on the HF score meaning that they are capable of control themselves to be in a relaxing state.…”
Section: Hrv Performances Of the Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the participant that had been undergone the training previously had been significantly resulted in a better HRV amplitude than before. Maximal performance control over the HRV can be obtained after series of approximately four sessions of training [12]. The students that have the good result on the HF score meaning that they are capable of control themselves to be in a relaxing state.…”
Section: Hrv Performances Of the Participantsmentioning
confidence: 99%
“…Recent researches [12] have publicized the consequence of HRV biofeedback to the development of some cognitive functions in both simulated and real industrial operators. Patients with coronary heart disease (CHD) have psychological stress exhibit decreased vagal control of heart rate (HR), as measured by spectral analysis of HR variability (HRV) [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sutarto, Wahab, and Zin (2010) showed in two different studies the beneficial effect of slow breathing training on the cognition in a group of university students acting as simulated operators, as well as in a group of real operators. In a first preliminary study, the university students showed a significant improvement in verbal memory and decision-making after the BFB training but not in cognitive flexibility (Sutarto et al 2010).…”
Section: Hrv Biofeedback Trainingmentioning
confidence: 99%
“…Both intellectual and non-intellectual factors such as fatigue, stress, motivation (Megaw 1979;Newell et al 2008;Sutarto et al 2010), and an individual's affective state (Sutarto et al 2013) can have their influence. To select an example, stress is an important moderating factor in cognitive performance and the concept knows a long research history.…”
Section: Cognitive Performance and Physiological Arousalmentioning
confidence: 99%
See 1 more Smart Citation